Determinants of Consumers’ Willingness to Purchase Generic Medicines - Mohd Redhuan Dzulkipli; Siti Noorsuriani Maon; Nor Sara Nadia Muhamad Yunus; Aziz Jamal; Nor Azzura Nordin (Information Management and Business Review, 2023)
In Malaysia healthcare costs have posed challenges to the sustainability of the country's dual healthcare system, it is crucial to learn about the factors influencing consumer preferences for generic medicines. The public healthcare system predominantly uses generic drugs, private healthcare providers often prescribe originator brands to their patients. This practice places financial burdens on patients who must fund their medication independently or through private medical insurance. Therefore, the main objective of this paper is to investigate the determinants affecting consumers' willingness to purchase generic medicine in Malaysia. Using convenience sampling, a total of 436 responses was obtained. Descriptive statistics and bivariate logistic regression analysis were employed to examine the influence of sociodemographic factors and individual knowledge on the willingness to purchase generic medicine. The results indicate that age, ethnicity, marital status, education level, household size and income significantly influence the consumers' willingness to purchase generic medicine. Notably, higher education levels and greater income were associated with a higher willingness to opt for generic medicine. Unexpectedly, variables measured by the Theory of Planned Behavior did not contribute substantially to the findings of this study. Nonetheless, individual knowledge was revealed as a significant determinant. To increase the uptake of generic medicines, this study recommends educational programs for both healthcare providers and patients, emphasizing the benefits and safety of generic medicine. This research contributes to the broader discussion on cost-effective healthcare solutions and informs policymakers and healthcare stakeholders in Malaysia.